Corrosion behavior and electrochemical properties of carbon steel, commercial pure titanium, copper and copper–aluminum–nickel alloy in 3.5% sodium chloride containing sulfide ions - H. Nady; M.M. El-Rabiei; M. Samy (Egyptian Journal of Petroleum)
In this research the electrochemical performance of Cu, Cu–10Al–10Ni, Cp-Ti and C-steel in 3.5% sodium chloride containing sulfide ions was investigated. Different electrochemical methods such as polarization technique and electrochemical impedance spectroscopy, EIS, were used. Surface examination and morphological studies were employed. The effect of immersion time of the different alloys was extensively studied by EIS. A comparison was made between the electrochemical stability of the different alloys in this media. Polarization measurements reveal that Cp-Ti and Cu–10Al–10Ni alloys possess lower corrosion rates than both Cu and carbon steel. EIS measurements, have shown that a more thicker and resistive passive film is formed on Cp-Ti alloy due to the formation of TiO2 film of duplex nature. The incorporation of Ni in the Cu2O barrier film leads to the stabilization of Cu–10Al–10Ni alloy and the stability is enhanced in the presence of Al. The thickness and resistance of the barrier layer formed on the alloy surfaces increase with the increasing the immersion time. The formation of such passive film on the surface of different alloys was discussed. An equivalent circuit model for the electrode/electrolyte interface under different conditions was proposed. The experimental impedance data were fitted to the theoretical data according to the proposed model.